A Conceptual Framework of Culturally-Based Planning for Sustainable Spatial Development in Indigenous Villages - Sunhadji, Richa Rahmaliya; Paikun, Paikun; Amdani, Selfin Anugrah; Rahmawati, Debby; Daniel, Basil David; Mudjanarko, Sri Wiwoho; Dewi, Deshinta Arrova (ASTONJADRO, 2026)
Indigenous villages face growing pressures from modernization and unplanned development, creating tensions between cultural preservation and spatial adaptation. This study develops a conceptual framework for culturally based planning in sustainable spatial development, using Kasepuhan Sinar Resmi, part of the UNESCO Global Geopark Ciletuh, as a case study. An integrative methodological design was employed, combining SWOT analysis for situational diagnosis, multi-criteria analysis (MCA) for structured prioritization, and the Delphi method for stakeholder consensus-building. Results show that socio-cultural values, particularly rituals, rice barns (leuit), and customary governance, emerged as the highest priority, confirming the central role of intangible heritage as active planning criteria. MCA indicated that culture anchors planning (40%), environment sustains it (35%), and economy complements it (25%), while the Delphi process demonstrated that authenticity can be reframed as a negotiated construct, reconciling preservation with modernization. The study produced a zoning model comprising a core preservation area, a culturally aligned buffer zone, and a sustainable development zone, offering both local solutions and globally transferable lessons. Theoretically, the research enriches heritage conservation discourse by operationalizing the concept of living heritage and advancing participatory governance as a mechanism for adaptive authenticity. Practically, it highlights the need to recognize customary authority as a legitimate planning infrastructure and to integrate cultural values into zoning regulations. The findings demonstrate that indigenous communities can transform modernization–preservation tensions into opportunities for adaptive resilience, providing insights applicable to other indigenous settlements worldwide.